2019
DOI: 10.1353/hpu.2019.0101
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Community-Engaged Research with Pacific Islander Communities in the US and USAPI: A Scoping Review

Abstract: This scoping review identifies the best practices of community-based participatory research with Pacific Islanders in the United States and United States Affiliated Pacific Islands. Eighty-four articles from January 2000 to December 2017 were included in the review. Best practices included the importance of engaging Pacific Islander community leaders as research staff, community coinvestigators, and community advisory board members. Best practices also focused on removing barriers to research by using particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 118 publications
(308 reference statements)
0
50
0
Order By: Relevance
“…Lee et al [ 3 ] found that among immigrant Asian subgroups, lower health literacy affects health outcomes. In previous research with Pacific Islanders including MI, researchers reported the need to clarify kinship as family extends to blood or not blood related [ 5 , 8 ]. In our study, participants did report that the family health history GCS postcard reflected multigenerational importance, yet it was missing the fullness of what is meant by family with the absence of male images on the postcard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al [ 3 ] found that among immigrant Asian subgroups, lower health literacy affects health outcomes. In previous research with Pacific Islanders including MI, researchers reported the need to clarify kinship as family extends to blood or not blood related [ 5 , 8 ]. In our study, participants did report that the family health history GCS postcard reflected multigenerational importance, yet it was missing the fullness of what is meant by family with the absence of male images on the postcard.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the aim is to maintain harmony within social family structures, often through reciprocal gestures of respect between a brother and a sister that are often misunderstood by some Chuukese Islanders and foreign visitors (pp. 149–150).” In a systematic review, McElfish et al [ 8 ] discussed about the importance of honoring the practices of Pacific Islander cultures, and this includes separating activities by sex due to the sensitivity of such topics. Furthermore, having a team member collecting the sensitive data information to be the same sex as the participant or patient would be culturally responsive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our current study, we did not find a statistically significant association between having any NSC and the likelihood of reporting MFH in either NHPI or NHW cancer survivors after adjusting for other covariates, although NHPIs reported a stronger association than NHWs. The collectivist cultural structure of NHPIs values social and spiritual inclusiveness . The lower NSC reported among NHPI cancer survivors may affect the psychological well being of cancer survivors independent of MFH, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…All study information documents used for recruitment, consent, and retention were developed in collaboration with Marshallese stakeholders (CAN and Marshallese bilingual study staff) using a CBPR approach [ 47 ]. Thirty women will be recruited by the Marshallese bilingual study staff, who will recruit at local clinics, faith-based organizations, and community-based organizations.…”
Section: Methodsmentioning
confidence: 99%